Exploring Gender Differences in Machiavellianism Using a Measurement Invariance Approach. Issue 2 (4th March 2021) - Collison, Katherine L.; South, Susan; Vize, Colin E.; Miller, Joshua D.; Lynam, Donald R.
Abstract: Research suggests that men and women differ on mean levels of Dark Triad personality constructs such as Machiavellianism, but few studies have investigated whether or not these differences are due to actual latent trait differences or bias in measurement. Further, recent research suggests important challenges associated with existing measures of MACH in terms of overlap with psychopathy and matching expert descriptions. The present study took a recently developed measure of Machiavellianism (the Five Factor Machiavellianism Inventory; FFMI), based on the five-factor model, and examined its invariance across gender. Strong (or scalar) factorial invariance was established, indicating that latent factor means can be compared between men and women using this measure. Mean-level differences showed that men had higher levels of latent factors related to antagonism and social dominance. In terms of total score, men reported significantly higher mean levels of Machiavellianism. The findings of the present study lend support to the notion that mean level differences in Machiavellianism across gender are not artifacts of measurement bias.